A simplified method for evaluating the reinforcing effect and efficiency of natural rubber based on the particle size of the combined particles formed by fillers and natural rubber latex
By judging the bonded rubber particle size formed by filler and natural latex and calculating the rubber particle size ratio, the complex and time-consuming evaluation method of rubber enhancement efficiency of fillers in the prior art is solved, and fast and accurate evaluation of enhancement effects and efficiency is achieved. It is suitable for a variety of fillers and preparation methods.
Patent Information
- Application Number
- CN202410169729.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-02-06
AI Technical Summary
The prior art lacks convenient, fast and intuitive and scientific methods to evaluate the efficiency of rubber reinforcement of fillers, and existing methods often require expensive equipment, toxic reagents or time-consuming and labor-intensive.
By judging the particle size of the bonded rubber particles formed by the filler and natural latex, calculate the particle size ratio, and judge the enhancement effect and enhancement efficiency of the filler on natural rubber. This method does not require subsequent treatment and is suitable for all reinforcement fillers commonly used in natural rubber.
It realizes the rapid and accurate judgment of the reinforcement effect and enhancement efficiency of fillers on natural rubber, simplifies the evaluation of rubber formula optimization and filler modification effect, and has the application potential of industrial production.
Smart Images

Figure CN118258727B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional natural rubber composite materials, and in particular to a simplified method for judging the reinforcing effect and efficiency of natural rubber based on the particle size of combined rubber particles formed by fillers and natural rubber latex. Background Art
[0002] Rubber is a polymer elastomer composed of linear macromolecules or linear macromolecules with branches. It has the advantages of good high elasticity, excellent fatigue strength, good electrical insulation, good wear resistance and heat resistance. It is widely used in electronics, transportation, aerospace, agriculture, medical care and daily life. The development of the rubber industry is not just the single development of a single industry, but involves the common development of multiple industries. Therefore, the scientific, rapid, standardized and diversified evaluation of rubber quality can better guarantee the service safety of rubber, which is of great significance in actual production and life.
[0003] Surface properties directly affect the physical adsorption or chemical bonding between fillers and rubber molecular chains, thereby affecting the interfacial bonding strength between the two phases, and further determining the reinforcing efficiency of the filler on the rubber matrix. Reinforcement efficiency refers to the degree to which the filler in the composite material improves the mechanical properties of the rubber matrix, often expressed as a percentage of mechanical property improvement. This patent uses 100% of the modulus of tensile stress to quantify the reinforcing efficiency.
[0004] At present, there is still a lack of a convenient, fast, intuitive and scientific evaluation method for the reinforcing efficiency of fillers on rubber. Existing evaluation methods are mainly divided into two categories. One is the evaluation of the interaction between fillers and rubber interfaces, which is obtained by testing the bound rubber content in the vulcanized rubber or the crosslinking density of the vulcanized rubber. This method not only requires the use of toxic reagents such as toluene, but also requires the rubber to be treated for three days of reaction, which is time-consuming and laborious. The second category is obtained by testing the mechanical properties of the vulcanized rubber, such as tensile properties, tear properties and abrasion properties. These tests are generally carried out in reference to national or industry standards. The test objects are rubber samples of specific size specifications that meet the standards and need to be completed under specific test equipment and specific test parameters. The changes in the mechanical performance indicators or structural parameters obtained are used to evaluate the changes in rubber properties with environmental parameters and time. There are problems such as sample processing, testing and data processing that are laborious and time-consuming.
[0005] Patent CN115266350A (application date July 29, 2022, publication date November 1, 2022) provides a test method for the permanent deformation of rubber under compression in a medium environment. The quality of the rubber is evaluated by placing the permanent deformation device under compression in a simulated environment. The following limitations exist: (1) Specific means and methods are required, which is time-consuming and labor-intensive. (2) Calibration experiments are required before quality evaluation, which takes a long time. (3) The sample size or test conditions affect the test results.
[0006] Patent CN115855635A (application date November 22, 2022, publication date March 28, 2023) provides a rubber quality evaluation method and system based on tensile fracture morphology analysis. This method is based on the analysis of the fracture morphology after the rubber is tensile fractured, divides the morphology into a curved area and a rough area, and associates the area proportion of each characteristic area with the tensile strength and elongation at break of the material to qualitatively and quantitatively evaluate the quality of the rubber. There are the following limitations: (1) The equipment used for evaluation is expensive and complicated to operate. (2) It is well known that morphological analysis based on scanning electron microscopy is carried out on selected micro-areas, which can easily lead to the problem of generalizing from a single case.
[0007] Patent CN115563803A (application date October 25, 2022, publication date January 3, 2023) provides a method for evaluating the service life of natural rubber. By substituting the torque value into the equivalent aging rate equation and the Van't Hoff formula, the service life of the rubber compound is obtained. There are the following limitations: (1) It needs to be calibrated through a large number of preliminary experiments before it can be used. (2) The test conditions will affect the test results.
[0008] In summary, the current evaluation methods for the efficiency of rubber reinforcement by fillers have the following limitations: ① It requires the use of expensive instruments and equipment or the use of toxic reagents, which results in high costs or is not environmentally friendly; ② Using performance parameters as evaluation indicators, sample processing, testing and data processing are time-consuming and laborious. Therefore, it is very necessary to propose new ideas or methods for evaluating the efficiency of rubber reinforcement by fillers. Based on the theory of filler-reinforced rubber, the present invention proposes a new evaluation method, which is significantly correlated with the results of the current evaluation method. The method of the present invention is applicable to all common reinforcing fillers of natural rubber, and is tested in a latex state without the need for subsequent treatment. Therefore, it is easy to evaluate the performance of rubber products before industrial production, quickly optimize rubber formulas, and efficiently evaluate the effect of filler modification. Summary of the invention
[0009] In view of the current lack of a convenient, fast, intuitive and scientific evaluation method for the reinforcing effect and efficiency of fillers on rubber, the present invention provides a simplified method for judging the reinforcing effect and efficiency of fillers on natural rubber based on the particle size of the combined rubber particles formed by fillers and natural rubber latex. It can quickly and accurately judge the improvement effect of fillers on the mechanical properties of natural rubber vulcanizates.
[0010] The present invention is achieved through the following technical scheme: a simplified method for judging the reinforcing effect of fillers on natural rubber based on the particle size of combined rubber particles formed by fillers and natural rubber latex, comprising the following steps:
[0011] ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.1. After the interaction between the two in the aqueous phase changes the particle size of the latex, dilute it into a latex test solution of a certain concentration;
[0012] ② Using an instrument capable of testing the particle size of the dispersion liquid to be tested in step ①, the particle size of the latex to be tested is measured, and then the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex at the same concentration without the filler are obtained, and the particle size ratio of the particles is calculated as x=d / d1, wherein d represents the average particle size of the combined particles formed by the filler and the natural latex, and d1 represents the average particle size of the pure natural latex at the same concentration without the filler;
[0013] ③ When the particle size ratio x≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x=1-1.07, the filler has a poor reinforcing effect on natural rubber prepared by various processes; when 1.14>the particle size ratio x>1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes.
[0014] As a further improvement of the technical solution of the method for judging the enhancement effect of the present invention, in step ①, the concentration range of the prepared latex test solution only needs to meet the test range of the particle size test analyzer used.
[0015] As a further improvement of the technical solution of the method for judging the enhancement effect of the present invention, in step ①, the prepared latex test liquid should be in a stable state without demulsification.
[0016] The present invention further provides a simplified method for judging the reinforcing efficiency of natural rubber based on the particle size of combined rubber particles formed by fillers and natural rubber latex, comprising the following steps:
[0017] ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.1. After the interaction between the two in the aqueous phase changes the particle size of the latex, dilute it into a latex test solution of a certain concentration;
[0018] ② Using an instrument capable of testing the particle size of the dispersion liquid to be tested in step ①, the particle size of the latex to be tested is measured, and then the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex at the same concentration without the filler are obtained, and the particle size ratio of the particles is calculated as x=d / d1, wherein d represents the average particle size of the combined particles formed by the filler and the natural latex, and d1 represents the average particle size of the pure natural latex at the same concentration without the filler;
[0019] ③ When the particle size ratio x≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x=1-1.07, the filler has a poor reinforcing effect on natural rubber prepared by various processes; when 1.14>particle size ratio x>1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes;
[0020] ④ Test the tensile stress value y of the modified filler / natural rubber vulcanizate prepared by a certain process of the modified filler obtained by at least two different modification processes respectively, and then substitute the tensile stress value y and the value of the particle size ratio x obtained in step ② into the following functional relationship:
[0021] y=a+bx
[0022] Where: a, b are constants;
[0023] The corresponding values of a and b are calculated, and then a specific functional relationship corresponding to the particle size of the combined rubber particles formed by the filler and the natural rubber latex is obtained to judge the reinforcing efficiency of the filler on the natural rubber prepared by various processes;
[0024] ⑤ According to steps ① and ②, the average particle size of the combined rubber particles formed by the modified filler of the filler obtained by other modification processes and the natural rubber latex is tested, and then the particle size ratio x is obtained. Then, the specific functional relationship obtained in step ④ is used to calculate the tensile stress value y of the modified filler / natural rubber vulcanizate, and the tensile stress value y' of the natural rubber vulcanizate prepared by the same process without adding the modified filler is tested, and then R is calculated according to the formula R = [(y-y') / y'] · 100%. When R ≦ 10%, the reinforcing efficiency of the modified filler on natural rubber is low; when R ≧ 20%, the reinforcing efficiency of the modified filler on natural rubber is high; when 20%>R>10%, the reinforcing efficiency of the modified filler on natural rubber is average.
[0025] As a further improvement of the technical solution of the method for judging the enhancement efficiency of the present invention, in step ①, the concentration range of the prepared latex test solution only needs to meet the test range of the particle size test analyzer used.
[0026] As a further improvement of the technical solution of the method for judging enhancement efficiency of the present invention, in step ①, the prepared latex test liquid should be in a stable state without demulsification.
[0027] As a further improvement of the technical solution of the method for judging the enhancement efficiency of the present invention, in step ④, the mass ratio of the modified filler to the natural rubber in the modified filler / natural rubber vulcanizate used in the tensile stress test is consistent with the mass ratio of the modified filler to the natural rubber in the natural rubber latex in step ①.
[0028] The technical solution provided by the present invention has the following advantages compared with the prior art:
[0029] (1) The present invention can quickly and accurately determine the reinforcing effect and efficiency of fillers on natural rubber. On the one hand, it can provide a scientific, accurate, fast and efficient evaluation method for the modification effect of fillers; on the other hand, it can lay a foundation for the scientific, accurate, fast and efficient optimization of rubber formulas. It is of great significance for promoting the application of fillers in the field of high-performance natural rubber.
[0030] (2) The present invention is applicable to all reinforcing fillers commonly used in natural rubber, such as graphene oxide, carbon black, silica, etc., and is applicable to natural rubber vulcanizates prepared by different preparation methods, such as mechanical blending method, solution blending method, etc., and has strong applicability.
[0031] (3) The preparation method of the test sample of the present invention is simple and environmentally friendly, without any stringent requirements. All the equipment involved are conventional and replaceable, so it has the advantages of being simple, green, and fast. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 The specific functional relationship formula for judging the reinforcing efficiency of graphene oxide on natural rubber prepared by various processes based on the particle size of the combined rubber particles formed by the modified graphene oxide and natural latex obtained in Example 1 and Example 2.
[0035] Figure 2 These are the X-ray diffraction curves (XRD) of the three modified graphene oxide / natural rubber compounds of Example 1.
[0036] Figure 3 Schematic diagram of the particle size change of graphene oxide / natural rubber latex and modified graphene oxide / natural rubber latex in the examples.
[0037] Figure 1 The specific functional relationship between the particle size of the combined colloid formed by the modified graphene oxide and natural latex obtained in Example 1 and Example 2 is used to judge the reinforcing efficiency of the graphene oxide on natural rubber prepared by various processes. Example 1 The specific functional relationship between the reinforcing efficiency of the graphene oxide on natural rubber obtained by three different modifiers is y=a+bx, where y is the tensile stress value of the graphene oxide / natural rubber vulcanizate, and x is the particle size ratio=(the average particle size of the combined colloid formed by the modified graphene oxide and natural latex obtained by different modification processes) / (the average particle size of the colloid of pure natural latex without the addition of the graphene oxide at the same concentration). Constant a=-1.747, constant b=5.607. Based on the functional relationship, the reinforcing efficiency of different modified graphene oxides on natural rubber obtained by different ratios of the same modifier and graphene oxide can be calculated by the particle size ratio x = (the average particle size of the combined particles formed by the modified graphene oxide and natural latex obtained by different modification processes) / (the average particle size of the pure natural latex without the modified graphene oxide at the same concentration) to obtain the tensile stress value y of the corresponding vulcanized rubber, and then obtain R. It can be seen that the calculated tensile stress value is consistent with the actual tensile stress value, indicating that the simplified method of judging the reinforcing effect and enhancement efficiency of fillers on natural rubber of the present invention has a high degree of accuracy. In addition, compared with the traditional evaluation method based on the content of the combined rubber and the evaluation method based on the cross-linking density of the vulcanized rubber, the method of the present invention saves time and effort and is green and environmentally friendly.
[0038] Figure 2 It shows that 9° is the (001) crystal plane peak of graphene oxide (GO), among which GC (hexadecyltrimethylammonium bromide modified graphene oxide / natural rubber) and GT (Tween 20 modified graphene oxide / natural rubber) have smaller 2θ, indicating that the natural rubber (NR) molecular chain is successfully inserted between the GO sheets, and the interlayer spacing becomes larger. 19° is the broad peak of NR itself, which has shifted, indicating that the introduction of GO particles has reduced the lattice parameter of NR, reduced the amorphous part, and increased 2θ. The broad peak shift in the NR / GC spectrum is more significant, indicating that the interaction between NR and modified GO in this system is the largest among the three mixed rubbers, followed by GT, and the worst is GS. This effectively corresponds to the average particle size of the combined particles formed by them with natural latex, and then corresponds to the performance of the vulcanized rubber, verifying the accuracy of the evaluation method of the present invention.
[0039] Figure 3It shows that under strong interfacial interaction, the particle size of the combined particles formed by modified GO and natural rubber latex is larger than that of the combined particles formed by unmodified GO and natural rubber latex. When the interfacial interaction is weak, the particle size of the combined particles formed by GO and natural rubber latex is closer to the particle size of pure natural rubber latex, so the ratio of the two is closer to 1. When the interfacial interaction is strong, there is an interfacial interaction between modified GO and natural rubber latex, which causes the modified GO to be adsorbed on the surface of natural rubber particles. Therefore, the average particle size of the combined particles formed by modified GO and natural rubber latex increases, and its ratio to the particle size of pure natural rubber latex particles increases accordingly, reaching a maximum of 1.18, such as Figure 1 . DETAILED DESCRIPTION
[0040] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0041] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0042] The present invention provides a specific embodiment of a simplified method for judging the reinforcing effect of a filler on natural rubber based on the particle size of a combined rubber particle formed by a filler and a natural rubber latex, comprising the following steps:
[0043] ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.1. After the interaction between the two in the aqueous phase changes the particle size of the latex, dilute it into a latex test solution of a certain concentration;
[0044] ② Using an instrument capable of testing the particle size of the dispersion liquid to be tested in step ①, the particle size of the latex to be tested is measured, and then the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex at the same concentration without the filler are obtained, and the particle size ratio of the particles is calculated as x=d / d1, wherein d represents the average particle size of the combined particles formed by the filler and the natural latex, and d1 represents the average particle size of the pure natural latex at the same concentration without the filler;
[0045] ③ When the particle size ratio x≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x=1-1.07, the filler has a poor reinforcing effect on natural rubber prepared by various processes; when 1.14>the particle size ratio x>1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes.
[0046] The present invention also provides a specific embodiment of a simplified method for judging the reinforcing efficiency of natural rubber based on the particle size of combined rubber particles formed by fillers and natural rubber latex, comprising the following steps:
[0047] ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.1. After the force between the two in the water phase causes the latex particle size to change, dilute it into a latex test solution of a certain concentration;
[0048] ② Using an instrument capable of testing the particle size of the dispersion liquid to be tested in step ①, the particle size of the latex to be tested is measured, and then the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex at the same concentration without the filler are obtained, and the particle size ratio of the particles is calculated as x=d / d1, wherein d represents the average particle size of the combined particles formed by the filler and the natural latex, and d1 represents the average particle size of the pure natural latex at the same concentration without the filler;
[0049] ③ When the particle size ratio x≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x=1-1.07, the filler has a poor reinforcing effect on natural rubber prepared by various processes; when 1.14>particle size ratio x>1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes;
[0050] ④ Test the tensile stress value y of the modified filler / natural rubber vulcanizate prepared by a certain process of the modified filler obtained by at least two different modification processes respectively, and then substitute the tensile stress value y and the value of the particle size ratio x obtained in step ② into the following functional relationship:
[0051] y=a+bx
[0052] Where: a, b are constants;
[0053] The corresponding values of a and b are calculated, and then a specific functional relationship corresponding to the particle size of the combined rubber particles formed by the filler and the natural rubber latex is obtained to judge the reinforcing efficiency of the filler on the natural rubber prepared by various processes;
[0054] ⑤ According to steps ① and ②, the average particle size of the combined rubber particles formed by the modified filler of the filler obtained by other modification processes and the natural rubber latex is tested, and then the particle size ratio x is obtained, and then the specific functional relationship obtained in step ④ is used to calculate the tensile stress value y of the modified filler / natural rubber vulcanizate; the tensile stress value y' of the natural rubber vulcanizate prepared by the same process without adding the modified filler is tested, and then R is calculated according to the formula R = [(y-y') / y'] · 100%. When R ≦ 10%, the reinforcing efficiency of the modified filler on natural rubber is low; when R ≧ 20%, the reinforcing efficiency of the modified filler on natural rubber is high; when 20%>R>10%, the reinforcing efficiency of the modified filler on natural rubber is average.
[0055] In the two simplified methods provided by the present invention for judging the reinforcing effect and efficiency of natural rubber based on the particle size of the combined rubber particles formed by the filler and the natural latex, in step ①, the concentration range of the prepared latex test liquid only needs to meet the test range of the particle size test analyzer used.
[0056] Furthermore, in step ①, the prepared latex test solution should be in a stable state without demulsification.
[0057] Furthermore, in step ④, the mass ratio of the modified filler to natural rubber in the modified filler / natural rubber vulcanizate used in the tensile stress test is consistent with the mass ratio of the modified filler to natural rubber in the natural rubber latex in step ①.
[0058] The specific embodiments of the present invention are described in detail below.
[0059] Embodiment 1:
[0060] ① GO was modified with three surface modifiers, hexadecyltrimethylammonium bromide, sodium dodecyl sulfate and Tween 20, and the modified GOs were named GC, GS and GT respectively. Natural rubber latex and the three modified GOs were mixed evenly at a mass ratio of 100:0.5, and prepared into a uniformly dispersed latex test solution with a concentration of 2.5 mg / L.
[0061] ② Use a particle size test analyzer to test the particle size of each latex test solution and obtain an average value. In this embodiment, the average particle size of the pure natural rubber latex particles obtained by the test is 369.7 μm. The average particle size of the combined particles formed by the three modified GO and natural rubber latex and the corresponding particle size ratio x are shown in Table 1.
[0062] ③ The particle size of the combined particles formed by the three modified GO and natural rubber latex all increased, among which the size of the combined particles of the GC modified system was the largest, indicating that its adsorption effect on the natural latex particles in the aqueous phase was the strongest. In this embodiment, the particle size ratio x of the average particle size of the combined particles of the GC modified system to the particle size of the pure natural rubber latex was 1.089, and the filler had a significant reinforcing effect on the natural rubber vulcanizates prepared by various processes. The measured results showed that the 100% tensile stress value y' of the pure natural rubber vulcanizate was 3.866MPa, and the 100% tensile stress y of GC / NR was 4.397MPa, R = [(4.397-3.866) / 3.866] · 100% = 13.7%, which was consistent with the reinforcing effect results obtained by the method of the present invention.
[0063] ④ After mixing the natural rubber latex and the three modified GOs at a mass ratio of 100:0.5, 10wt.% flocculant CaCl2 solution was added to break the emulsion, and the mixture was dried in an oven at 50°C to constant weight. In an internal mixer, after mixing for 4 minutes at 110°C and 40rpm, 2g of vulcanization accelerator N-(diethylene oxide)-2-benzothiazole sulfonamide, 2g of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, and 2g of antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer were added and mixed for 4 minutes, then 5g of activator zinc oxide and 2g of softener stearic acid were added and mixed for 4 minutes, and 60g of reinforcing filler carbon black was added and mixed for another 4 minutes, and the rubber was discharged. After the rubber compound cools to room temperature, transfer it to an open mill and mix it at 60℃. After it is evenly dispersed, add 2g of sulfur and mix it evenly. Then, pass it through the mill until there are no bubbles in the rubber compound. The total mixing time is 10min. After 24h of mixing, place the mixed rubber in a mold and vulcanize it at 150℃*15MPa for 5min (t c90 ), and three modified GO / natural rubber vulcanizates were obtained, among which t c90 Measured by rubber processing analyzer (RPA). The tensile stress was obtained by tensile testing with a universal tensile testing machine (AL-7000-SGD, High Speed Rail Testing Instrument Co., Ltd.). The tensile performance test standard is ISO 37-2005, and the tensile rate is 500 mm / min.
[0064] The specific functional relationship of the graphene oxide reinforcement efficiency on natural rubber was obtained by modifying graphene oxide with three different modifiers, y=a+bx, where y is the tensile stress value of the graphene oxide / natural rubber vulcanizate, and x is the particle size ratio of the rubber particles=(the average particle size of the combined rubber particles formed by the modified graphene oxide and natural latex obtained by different modification processes) / (the average particle size of the rubber particles of pure natural latex without adding the graphene oxide at the same concentration). Constant a=-1.747, constant b=5.607. The subsequent Example 2 directly uses this specific functional relationship to calculate the tensile stress values of the modified graphene oxide / natural rubber vulcanizate obtained by different modification processes, and the results are shown in FIG. Figure 1 Further analysis shows that the filler-restricted rubber content in the GC-modified vulcanized rubber is the largest, so the combined rubber content also has the maximum value. Figure 2 It can be seen that the interfacial interaction between GC-modified graphene oxide and natural rubber in the rubber mix is the strongest, indicating that the law of the present invention is clearly reflected in the natural rubber mix, which effectively corresponds to the average particle size of the combined rubber particles formed by them with natural latex, and then corresponds to the performance of the vulcanized rubber, which also verifies the reliability of the evaluation method of the present invention.
[0065] Table 1 The particle size and particle size ratio of the bound rubber particles in the latex of Example 1, as well as the 100% tensile stress, 300% tensile stress, bound rubber content, and crosslinking density of the vulcanized rubber
[0066]
[0067]
[0068] Embodiment 2:
[0069] ① Graphene oxide was modified with surface modifier hexadecyltrimethylammonium bromide in different mass ratios with GO, and the mass ratios of modifier to graphene oxide were 1:1, 2:1, 3:1, 4:1, 5:1 and 6:1. Natural rubber latex and modified graphene oxide obtained by different modification processes were mixed uniformly at a mass ratio of 100:0.5 and prepared into a uniform latex test solution with a concentration of 2.5 mg / L.
[0070] ② Use a particle size test analyzer to test and obtain the average particle size of each latex test solution. In this embodiment, the average particle size of the pure natural rubber latex obtained by the test is 369.7 μm. The size of the combined particles formed by the modified GO and the natural rubber latex and the particle size ratio x are shown in Table 2.
[0071] ③ In this embodiment, the particle size of the combined colloid particles formed by the modified graphene oxide and natural rubber latex obtained by hexadecyltrimethylammonium bromide in a mass ratio of 2:1 is the largest, indicating that it has the strongest adsorption effect on the natural latex particles in the aqueous phase. Its particle size ratio x = 1.178, indicating that the modified GO has a good reinforcing effect on natural rubber. In this embodiment, the 100% tensile stress value y' of pure natural rubber vulcanizate is 3.866MPa, and the 100% tensile stress value y of the graphene oxide / NR vulcanizate modified by hexadecyltrimethylammonium bromide in a mass ratio of 2:1 is 4.453MPa, R = [(4.453-3.866) / 3.866] · 100% = 24.9%, which is consistent with the enhancement results obtained by the method of the present invention. In addition, the particle size of the GC modified system is positively correlated with the variation of the particle size of the natural rubber latex, the conventional binding rubber content and the variation of the crosslinking density, indicating the reliability of the method of the present invention. ④ The natural rubber latex and the different modified graphene oxides were mixed uniformly at a mass ratio of 100:0.5, and 10wt.% flocculant CaCl2 solution was added to break the emulsion, and dried in an oven at 50°C to constant weight. In an internal mixer, mix for 4 minutes at 110°C and 40rpm, then add 2g of vulcanization accelerator N-(diethylene oxide)-2-benzothiazole sulfonamide, 2g of antioxidant N-(1-methylisopentyl)-N'-phenyl-p-phenylenediamine, 2g of antioxidant 2,2,4-trimethyl-1,2-dihydroquinoline polymer and mix for 4 minutes, then add 5g of activator zinc oxide and 2g of softener stearic acid and mix for 4 minutes, add 60g of reinforcing filler carbon black and mix for another 4 minutes, and discharge the rubber. After the rubber is cooled to room temperature, transfer it to an open mixer and mix at 60°C. After evenly dispersing, add 2g of sulfur, mix evenly, and pass it through the mixer until there are no bubbles in the rubber. The total mixing time is 10 minutes. After stopping the mixing for 24 hours, place the mixed rubber in a mold and vulcanize it at 150°C*15MPa for 5 minutes (t c90 ), then the modified GO / natural rubber vulcanizate is obtained, where t c90 Measured by rubber processing analyzer (RPA). The tensile stress was obtained by tensile testing with a universal tensile testing machine (AL-7000-SGD, High Speed Rail Testing Instrument Co., Ltd.). The tensile performance test standard is ISO 37-2005, and the tensile rate is 500 mm / min.
[0072] ⑤ The functional relationship between the particle size ratio of the known rubber particles and the 100% tensile stress of the rubber composite material is y=a+bx. According to a=-1.747, b=5.607 obtained in Example 1 and the particle size ratio x obtained in step ③, the tensile stress value y of the modified graphene oxide / natural rubber vulcanizate obtained by the modification process is calculated, and then R=[(y-y') / y']·100% is calculated. The results are shown in Table 2. It can be seen that the calculated tensile stress value is highly consistent with the actual value, indicating that the reinforcing efficiency of other fillers of the natural rubber composite material can be judged based on the combined particle size formed by it and the natural latex using this functional relationship, avoiding subsequent processing, and facilitating the evaluation of rubber products before industrial production, rapid optimization of rubber formulas, and efficient evaluation of filler modification effects.
[0073] Table 2 The particle size and particle size ratio of the bound rubber particles in the latex of Example 2, as well as the 100% tensile stress, 300% tensile stress, bound rubber content, and crosslinking density of the vulcanized rubber
[0074]
[0075] The above is only a specific implementation of the present invention, which enables those skilled in the art to understand or implement the present invention. Although detailed descriptions are given with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments, and they should all be covered by the protection scope of the claims.
Claims
1. A simplified method for judging the reinforcing effect of fillers on natural rubber based on the particle size of the combined rubber particles formed by fillers and natural rubber latex, characterized in that: The following steps are involved: ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.
1. After the force between the two in the water phase changes the particle size of the latex, dilute it into a latex test solution of a certain concentration. The prepared latex test solution should be in a stable state without demulsification; ② Use an instrument capable of measuring the particle size of the dispersion to measure the particle size of the latex obtained in step ①, and then obtain the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex with the same concentration without the filler, and calculate the particle size ratio x = d / d1, where d represents the average particle size of the combined rubber particles formed by the filler and natural rubber latex, and d1 represents the average particle size of the rubber particles of pure natural rubber latex without the filler at the same concentration; ③ When the particle size ratio x ≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x =1-1.07, the filler has poor reinforcing effect on natural rubber prepared by various processes; when 1.14>particle size ratio x When >1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes.
2. The simplified method for judging the reinforcing effect of filler on natural rubber based on the particle size of the combined rubber particles formed by the filler and the natural rubber latex according to claim 1, characterized in that: In step ①, the concentration range of the prepared latex test solution only needs to meet the test range of the particle size test analyzer used.
3. A simplified method for judging the reinforcing efficiency of natural rubber based on the particle size of the combined rubber particles formed by the filler and the natural rubber latex, characterized in that: The following steps are involved: ① Mix the natural rubber latex and filler in a mass ratio of 100:5-0.
1. After the force between the two in the water phase changes the particle size of the latex, dilute it into a latex test solution of a certain concentration. The prepared latex test solution should be in a stable state without demulsification; ② Use an instrument capable of measuring the particle size of the dispersion to measure the particle size of the latex obtained in step ①, and then obtain the average particle size of the combined particles formed by the filler and the natural latex and the average particle size of the pure natural latex with the same concentration without the filler, and calculate the particle size ratio x = d / d1, where d represents the average particle size of the combined rubber particles formed by the filler and natural rubber latex, and d1 represents the average particle size of the rubber particles of pure natural rubber latex without the filler at the same concentration; ③ When the particle size ratio x ≧1.14, the filler has a good reinforcing effect on natural rubber prepared by various processes; when the particle size ratio x =1-1.07, the filler has poor reinforcing effect on natural rubber prepared by various processes; when 1.14>particle size ratio x When >1.07, the filler has a general reinforcing effect on natural rubber prepared by various processes; ④ Test the tensile stress value y of the modified filler / natural rubber vulcanizate prepared by a certain process of the modified filler obtained by at least two different modification processes, and then compare the tensile stress value y and the particle size ratio of the rubber particles obtained in step ② x The value of is substituted into the following functional relationship: ; Where: a , b is a constant; Calculate the corresponding a and b The value of is used to obtain a specific functional relationship corresponding to the particle size of the combined rubber particles formed by the filler and the natural rubber latex to judge the reinforcing efficiency of the filler on the natural rubber prepared by various processes; In step ④, the mass ratio of the modified filler to the natural rubber in the modified filler / natural rubber vulcanizate used in the tensile stress test is consistent with the mass ratio of the modified filler to the natural rubber in the natural rubber latex in step ①; ⑤ According to steps ① and ②, the average particle size of the combined particles formed by the modified filler and natural rubber latex obtained by other modification processes and the particle size ratio of the particles are obtained. x , and then use the specific functional relationship obtained in step ④ to calculate the tensile stress value y of the modified filler / natural rubber vulcanizate; test the tensile stress value y' of the natural rubber vulcanizate prepared by the same process without adding the modified filler, and then calculate R according to the formula R=[(y-y') / y']•100%. When R≦10%, the reinforcement efficiency of the modified filler on natural rubber is low; when R≧20%, the reinforcement efficiency of the modified filler on natural rubber is high; when 20%>R>10%, the reinforcement efficiency of the modified filler on natural rubber is average.
4. The simplified method for judging the reinforcing efficiency of natural rubber based on the particle size of the combined rubber particles formed by the filler and the natural rubber latex according to claim 3, characterized in that: In step ①, the concentration range of the prepared latex test solution only needs to meet the test range of the particle size test analyzer used.
Citation Information
Patent Citations
Butadiene rubber reinforced resin and its composition
JP2002003548A
Diene-based rubber composition
JP2012012514A